Violence as a Subject of Social Science II The Structure of Opportunities and Rational Expectations - Mario Domínguez Sánchez-Pinilla; Isis Sánchez Estellés (Budapest International Research and Critics University, 2021)
After cited several types of violence in part I, they do not have the same significance, neither the same meaning nor the same geopolitical scale. Maybe, specificity of political violence consists of its occurrence when relations are no longer conceivable or negotiable not even institutionalized or instituted, in other words, when symbolization fails and public spaces where violence could be debated don't exist or are fragmentary or unbalanced.